Problems in the Management and Operation of Academic Libraries in Poland during the Transiton Period - Jazdon, Artur (My University, 1994)
libraries in Poland proves that old organizational structures, procedures and habits should all go or be changed. To accelerate this change, changes in legal regulations and library legislation are necessary, and an increase in resources allocated to science and education unavoidable. Our ultimate goal is to maintain and develop the Library’s position as the University’s principal information provider in support of teaching and research and to enhance its standing as one of the leading academic research libraries in Poland. But, what is also very important, librarians themselves, especially senior staff and managerial staff in Polish libraries, should realize the new function of libraries and be aware of the expectations of their users and of the ways to meet them. These factors, combined with inevitable automation of library procedures, should result in the years to come in a complete change in the appearance of Polish libraries.